Patterns of Verbal Aggression on Social Media Platform X in Indonesia: A Thematic Analysis of User Motivations and Emotional Responses - Maisarah Pendri; Syarifatul Hidni Rafli; Niken Hartati (Da'wa Faculty of Islamic State University Salatiga, 2025)
Cyber ​​aggression has become a growing concern in digital spaces due to its negative impact on mental health, as repeated exposure to aggressive online interactions can contribute to anxiety, depression, emotional distress, and low self-esteem. Unlike face-to-face communication, cyber aggression often occurs publicly and continuously, increasing psychological pressure on individuals involved. Social media platforms such as X provide interactive environments where anonymity, rapid information exchange, and polarized discussions may encourage verbal aggression. This study aims to identify patterns of verbal aggression on the social media platform X in Indonesia by examining its causes, emotional responses, and behavioral motives. Using a qualitative approach with thematic analysis, data were collected from 391 active users of the platform. These factors interact with users' emotional states, leading to impulsive and hostile responses. Many perpetrators reported experiencing a sense of emotional relief after engaging in verbal aggression, indicating that such behavior may function as a maladaptive coping strategy for emotional regulation. Verbal aggression was primarily motivated by emotional expression and social criticism. These findings highlight the importance of strengthening digital literacy and ethical communication to foster healthier and more respectful online interactions.